Parametric Study of a Soil Erosion Control Technique: Concrete Lozenges Channels - Latifa El Bouanani; Khadija Baba; Ghizlane Ardouz; Fatima Ezzahraa Latifi (Salehan Institute of Higher Education, 2022)
A new technique,